Comparison of ox-LDL Levels in Diabetic Patients with Normo-, Micro-, and Macroalbuminuria with Their First Degree Relatives and the Healthy Control Group - Parisa Behzadi; Firouzeh Torabi; Massoud Amini; Ashraf Aminorroaya (International Journal of Endocrinology)
Oxidized low density lipoprotein (ox-LDL) is a product of oxidative stress. In this cross-sectional study, we compared the ox-LDL concentrations in diabetic patients with normoalbuminuria (n=28), microalbuminuria (n=28), and macroalbuminuria (n=28) with their first degree relatives (n=28) and healthy control people (n=31). They were selected by consecutive patient selection method. The ox-LDL level was assayed using ELISA. We measured blood pressure, lipid profile, fasting plasma glucose (FPG), and HbA1c in all groups. There was no significant difference in ox-LDL concentrations among normoalbuminuric, microalbuminuric, and macroalbuminuric diabetic groups. In diabetic patients with micro- and macroalbuminuria, ox-LDL concentration was higher than their first degree relatives (P=0.04 and P=0.03) and control group (P=0.001 and P=0.03, resp.). In normoalbuminuric diabetic persons, ox-LDL concentration was just higher than that of healthy people (P=0.02). There was no statistically significant difference in ox-LDL levels between normoalbuminuric diabetic patients and their first degree relatives. In conclusion, the presence and progression of albuminuria in diabetic patients are not related to ox-LDL concentration and genetic predisposition influences the plasma OX-LDL level. Larger sample size is needed to confirm this conclusion in future studies.